Combined histone deacetylase and cyclooxygenase inhibition achieves enhanced antiangiogenic effects in lung cancer cells12. Issue 3 (28th November 2011) - Wang, Xiaoqi; Li, Guangyuan; Wang, Antai; Zhang, Zhenfeng; Merchan, Jaime R.; Halmos, Balazs
Abstract Prostaglandin E2 (PGE2) is an important pro‐angiogenic and pro‐proliferative cytokine and the key enzymes modulating its levels, cyclooxygenase (COX)‐2 and 15‐hydroxyprostaglandin dehydrogenase (15‐PGDH) play important opposing roles in carcinogenesis. Previously we found loss of 15‐PGDH expression in lung cancer and its reactivation leads to strong in vivo tumor‐suppressive effect via an antiangiogenic mechanism. Here, we find that HDAC inhibitors (HDACI), such as trichostatin A (TSA) and vorinostat could reactivate 15‐PGDH expression but overall induce PGE2 generation and this is the result of concomitant induction of COX‐1 and ‐2 leading to functional promotion of endothelial cell proliferation and capillary formation. Direct TSA treatment inhibits endothelial cell proliferation and capillary formation in our study in line with prior reports as HDACIs have been shown to directly inhibit angiogenesis. The elevation of PGE2 levels induced by HDACI is potently neutralized by indomethacin (INN) or Celecoxib co‐treatment and accordingly, angiogenesis is more effectively inhibited when using conditioned medium of co‐treatment than either alone confirming that this effect is mediated via the PGE2 axis. Accordingly, blockage of EP2/4 receptors mitigates the stimulation of angiogenesis by excessive PGE2 generation mediated by TSA. In this study, we identify a potentially adverse effect of HDACIs through induction of both 15‐PGDH and COX‐2 leading to elevated PGE2 levels and thereby stimulation of angiogenesis. Co‐treatment of TSA and INN shows more potent anti‐angiogenic effects by inducing 15‐PGDH and inhibiting COX‐2. Overall, our results suggest that combined HDACI and COX inhibition should be explored clinically to achieve more meaningful benefits from HDACI therapy in lung cancer. © 2011 Wiley Periodicals, Inc.